Analisis Wacana Kritis Sara Mills pada Lirik Lagu Wanita Karya Upiak Isil - Mahsusi, Juni (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research aims to find out the representation of emancipation in the lyrics of the song Wanita Upiak Isil. This research uses qualitative method with Sara Mills critical discourse study. The data source in this research is the lyrics of the song Wanita Upiak Isil. The data source comes from the spotify site and video clips on the youtube channel. Data in the form of song lyrics are analyzed using Sara Mills' perspective. The data collection technique uses the technique of simak catat. The results of the research on the representation of emancipation in the lyrics of the song Wanita Upiak Isil found the position as subject-object more than the position of the reader. The most subjects are women and the least subjects are husbands (men). The most subjects represent the lives of married women. Women experience many demands but are often not given equal rights. Meanwhile, the overall object of the couplet is more forms of independence. Other objects represent a woman's skill in working. The position of the reader is found in the form of greeting “ma'am” used by the author to address the reader or listener of the song.